The effect of Endorsments and Social Media Marketing on Consumer Purchasing Decisions at Anna Online Shop - Mursida, Mursida; Uleng, Budiarti Putri; Abel, Abel; Rembulan, Andi; Alfarisih, Alfarisih; Tasya, Nanda (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
An endorsement is a form of support or recommendation given by an individual (usually a public figure, celebrity, or influencer) for a product, service, or brand. Endorsements are typically made by expressing satisfaction or the benefits experienced from using the product, either directly or through media such as advertisements, social media, or testimonials. This study aims to investigate the influence of endorsement and social media marketing on consumer purchasing decisions at Anna Online Shop, both simultaneously and partially. Anna Online Shop is a business operating in the sale of cosmetics, skincare, and makeup through physical stores and digital platforms such as Shopee and Instagram. This study employs a quantitative approach with data collection techniques through a questionnaire administered to 30 respondents who are active consumers. Data were analysed using validity and reliability tests, multiple linear regression analysis, F-tests, t-tests, and determination coefficients. The results indicate that, simultaneously, endorsements and social media marketing significantly influence purchasing decisions. However, partially, only social media marketing has a significant influence, while endorsements do not. This indicates that consumers respond more to information conveyed through social media than to the influence of public figures. These findings imply that an effective marketing strategy for Anna Online Shop is to optimise the use of social media as a means of communication, promotion, and interaction with consumers to enhance purchasing decisions.